Implementation of membrane processes of underground water treatment to the national public supply system as a method of reducing the elimination of resources with increased chloride concentrations - Zimoch, Izabela; Koszyka, Agata (Instal, 2023)
This article analyzes the potential use of membrane technologies in collective water supply systems as a means to mitigate the need for eliminating deep-water intakes with increased salinity from raw material resources for drinking water production. The assessment of the viability of reusing previously eliminated intakes was conducted in two directions: from the perspective of implementing a different technology dedicated to treating these waters and from the standpoint of technological optimization of the process, as well as in terms of the design and planning assumptions for the investment task.
Keywords: brackish water; water supply systems; deep water treatment; collective drinking water supply